The Role of Smart Technology in Improving Work Safety in the Construction Environment - Ady Purwoto; Daisy Debora Grace Pangemanan; Fandel Maluw (CV. Get Press Indonesia, 2024)
According to data from the International Labor Organization (ILO), the construction industry accounts for nearly 20% of all workplace accidents that occur worldwide. This emphasizes the importance of continued efforts to improve work safety in this sector (Artha Safety, 2024). In addition, the application of smart technology can also help improve operational efficiency, enable faster identification of risks, and enable more effective interventions before accidents occur. Therefore, this research aims to take a closer look at the role of smart technology in improving work safety in the construction environment. This research used a combination of quantitative and qualitative methods. Literature study, primary data collection, and data analysis are the three main stages of this research. From the available data, it can be seen that the adoption of smart technologies, including AI, IoT, and wearable devices, has a significant impact on reducing accidents in the construction sector. Not only a decrease in fatal accidents, but also an increase in workers' awareness of physical conditions and potential hazards on the job site. However, some challenges such as worker resistance and implementation costs still need to be overcome through education and management support. Implementing these technologies requires a comprehensive approach, including intensive training and education for workers, as well as management support to overcome resistance and implementation cost challenges. This investment in smart technology will ultimately lead to a safer, more efficient and productive work environment in the future.